Maintenance management model to increase availably in a metalworking SME applying TPM, SMED and PDCA - Espinoza-Huamash, Mirella (2022)
The variability of demand has led metalworking SMEs to develop more efficient processes. Therefore, increasing availability is a necessity to maintain competitiveness in the market. The main problem of the sector is the deficient maintenance system that involves machine and operator performance, causing losses in 8% of profit. Therefore, a maintenance management model is implemented, where the basis consists of improving the work environment and operator performance through 5S and TPM (Safety, Health and Environment). Subsequently, the disuse and setup time of each machine is reduced through the application of SMED, autonomous and preventive maintenance. The level of availability was increased by 4% and continuous improvement was applied to the indicators, which further increased availability by 2%. In summary, the successful implementation of the model depends not only on the diagnosis of the machines, but also on the commitment of the operator and management.